2019
DOI: 10.1111/den.13290
|View full text |Cite
|
Sign up to set email alerts
|

Value of contrast‐enhanced harmonic endoscopic ultrasonography with enhancement pattern for diagnosis of pancreatic cancer: A meta‐analysis

Abstract: Background Current imaging modalities are limited in their ability to distinguish pancreatic cancer (PC) from non‐neoplastic pancreatic lesions. The diagnostic use of contrast‐enhanced endoscopic ultrasonography (CE‐EUS) has increased, and its utility has been reported. Recently, contrast‐enhanced harmonic EUS (CH‐EUS) was reported to facilitate imaging of parenchymal perfusion and microvessels in pancreatobiliary diseases, leading to a high diagnostic accuracy for PC. The present meta‐analysis aims to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 27 publications
1
56
0
Order By: Relevance
“…Yamashita et al [196] focused on CE-EUS and reported that its sensitivity and specificity for differentiating ductal carcinomas from the other tumors with CE-EUS were 93% and 80%, respectively. Regarding CE-EUS with Sonazoid, Kitano et al [197] reported that CE-EUS-depicted hypoenhancement diagnoses ductal carcinomas with a sensitivity and specificity of 95.1% (92.7%-96.7%) and 89.0% (83.0%-93.1%), respectively [197].…”
Section: Strength Of Evidencementioning
confidence: 99%
“…Yamashita et al [196] focused on CE-EUS and reported that its sensitivity and specificity for differentiating ductal carcinomas from the other tumors with CE-EUS were 93% and 80%, respectively. Regarding CE-EUS with Sonazoid, Kitano et al [197] reported that CE-EUS-depicted hypoenhancement diagnoses ductal carcinomas with a sensitivity and specificity of 95.1% (92.7%-96.7%) and 89.0% (83.0%-93.1%), respectively [197].…”
Section: Strength Of Evidencementioning
confidence: 99%
“…The utility of quantitative evaluation of enhancement patterns using TICs in the differential diagnosis of pancreatic masses has been reported [23,[26][27][28][29]. In four meta-analyses, the pooled sensitivity and specificity of CE-EUS in the diagnosis of pancreatic cancer were 91-93% and 80-88%, respectively [30][31][32][33]. In addition, Yamashita et al [34] reported that the sensitivity of CE-EUS for the detection of pancreatic cancer in small pancreatic masses of 11-20 mm was significantly better than that of MDCT and MRI (95% compared to 78%, and 73%, respectively), and that the sensitivity of CE-EUS in pancreatic masses of 10 mm or less was also significantly better than that of MDCT (70% and 20%, respectively).…”
Section: Eus For Differential Diagnosis Of Pancreatic Cancermentioning
confidence: 99%
“…focused on CE-EUS and reported that its sensitivity and specificity for differentiating ductal carcinomas from the other tumors with CE-EUS were 93% and 80%, respectively. [ 196 ] Regarding CE-EUS with Sonazoid, Kitano et al . reported that CE-EUS-depicted hypoenhancement diagnoses ductal carcinomas with a sensitivity and specificity of 95.1% (92.7%–96.7%) and 89.0% (83.0%–93.1%), respectively.…”
Section: Hapter 6: O Ther O mentioning
confidence: 99%